Integrasi Kearifan Lokal dalam Kurikulum PAI dan Dampaknya terhadap Identitas Keagamaan serta Partisipasi Masyarakat - Ridha Kurniawan; Usman Usman; Nor Fadhilah (Journal Innovation In Education, 2026)
This study analyzes the integration of local wisdom values into the curriculum and teaching materials of Islamic Religious Education (PAI) and its impact on students’ religious identity and community participation. Using a qualitative approach with case study and phenomenological methods, the research was conducted in Sungai Ambawang involving PAI teachers, principals, students, community leaders, and parents. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through source, technique, and time triangulation, as well as member checking. The findings show that local wisdom is integrated through syllabi, lesson plans, modules, and contextual materials containing values of mutual cooperation, deliberation, courtesy, tolerance, and social solidarity, especially in ethics, social interaction, and Islamic cultural history. Implementation occurs through contextual learning, group discussions, and social projects based on religious and community activities. This integration strengthens students’ religious identity, promotes tolerance and religious social behavior, and increases community participation. The study concludes that local wisdom-based PAI supports contextual, inclusive, and culturally rooted learning for sustainable Islamic education development locally.